PENGARUH KEBIJAKAN MODAL KERJA TERHADAP RETURN ON INVESTMENT PADA INDUSTRI SEMEN DI BURSA EFEK INDONESIA PERIOD[ 2003-2010 - R. Adisetiawan (Jurnal Ilmiah Universitas Batanghari Jambi, 2011)
This research aim to know do policy of working capital have an effect on to Return On Investment (ROI)  at Cement  Industry which  listed  in  Indonesia Stock Exchange.  Etmten  in  popullation  cement Emiten the taken  amount  to  3  (three)  emiten  the  cement  industry  listed  in  Indonesia  Stock Exchange wtth  period  of research  between of 2003  up to year  of 20!0.  Analysis method  the used  is Multiple Linear Regression.The data  used  in   this  research   from   the  documenation   study   on  Indonesian   Capital  MarketDirectory and www.1sx,co id  Research design model  ts  nssociatif design, in  this case associatif design the used is causal associatif that is existence of causality between one vanehle with other vanabte.  This research is cencus type where all populatJons in the cement industry listed in Indonesia Stock Exchangefrom 2003 until 20!0 (during 8 year). The  variable used in this research  consist of current ratio (X1), working capita!  turnover  ratio (X2),   current assets to  total  assets (X3),  current liabihties  to  total  assets ratio  (Xi)  is  while  dependen  varible is return on  mvestment  (Y).  Method analysis  used  is  Mulllple Linear  Regression  Analysis   The  result indicate  that from some  working capital  policy as of current ratio, work.mg capital  turnover  ratio,  current essers'to  total  assets and current  liabilities  to  total assetsratio   simu!tanly   there   are  the   influence   significant   to  the   profitability   represented   by  Return  on Investment.  Partially show only vanabte current ratio and work.mg capital turnover ratio with explamed by variation the expressed in Adjusted R Square equal to 79 percent is while the rest equal to 21  percent influenced by other variable which is not e:-.p!mned by this research  model.  Research result pursuant to hypothesis  test  indicate  that  between  some  element  policy  of the  working  capital  is  most dominant inOuence  the  Return on  Investment  al the  cement  industry  of listed  in  Indonesia  Stock  Exchange is current  assets to  total  assets ratio. There  by for  finance  manager  and investor  have to  can and listen carefully to see changes that  happened in  company especially  concerning management  of the  working capital  started from planning,  compilation,  execution and observation of itself working capital as well as for investor in domg decision ofmvesment require to consider the factor· working capital factor. Keyword:  working capital,  current ratio,  return on mvemncnt,  working capital turnover.